Clinical outcomes of an integrated wound care protocol for diabetic foot ulcers ‒ a prospective study - Santoso, Dadi; Kumar Muniandy, Rajesh; Widyaswara Suwaryo, Putra Agina (Rzeszów University Press, 2026)
Introduction and aim. Diabetic foot ulcers (DFUs) are serious complications of diabetes, often leading to infection and amputation. This study evaluated the clinical outcomes of an integrated wound care protocol in patients with DFUs. Material and methods. A prospective cohort study was conducted among 225 patients with type 2 diabetes and Wagner grade 1–3 DFUs at PKU Muhammadiyah Hospital, Indonesia, between February and September 2024. All patients received a standardized integrated wound care protocol, including wound bed preparation, debridement, infection control, moisture balance, nutritional counseling, patient education, and ulcer offloading. The primary outcome was complete wound healing at 12 weeks; secondary outcomes were wound area reduction, BWAT score improvement, pain reduction, and infection control. Results. By week 12, 157 patients (69.8%) achieved complete healing. Mean wound area decreased from 6.8±3.2 cm² to 1.2±1.5 cm² (p<0.001), BWAT scores improved from 28.4±4.1 to 13.6±3.8 (p<0.001), and pain scores declined from 5.8±1.6 to 2.1±1.1 (p<0.001). Infection prevalence dropped from 45.3% to 12.4% (p<0.001). Healing was highest in Wagner grade 1 (83.1%), compared with grade 2 (69.7%) and grade 3 (47.1%). Conclusion. The integrated wound care protocol significantly improved healing, reduced wound size and pain, and controlled infection in DFU patients. These findings support its incorporation into routine multidisciplinary DFU management.
The study was approved by the Ethics Committee of the Faculty of Health and Sciences, Universitas Muhammadiyah Gombong, Indonesia (Approval No. 12/EC/KEPK-FKUMS/I/2024).
Keywords: clinical outcomes; diabetic foot ulcer; integrated wound care; prospective study; wound healing